Pengaruh senam Prolanis terhadap penyandang hipertensi - Lumempouw, Deiby O.; Wungouw, Herlina I.S; Polii, Hedison . (Universitas Sam Ratulangi, 2016)
Abstract: Hypertension is one of the degenerative diseases commonly found in Indoensia. It is characterized by an increase of blood pressure above its normal level and is caused by various factors. This study aimed to obtain the influence of Prolanis exercise on hypertensive patients. This was an experimental field study with a pre-post test one group design conducted for 4 weeks. There were 25 respondents in this study obtained by using purposive sampling. Data were analyzed with the paired t-test.The results showed that there were significant differences between before and after two-times-per-week Prolanis exercise in systolic blood pressure ( p = 0,003 < Î± =0,001) and in diastolic blood pressure ( p = 0,002 < Î± =0,001). There were significant differences before and after three- times-per-week Prolanis exercise in systolic blood pressure (p = 0,000 < Î± = 0,01) and in diastolic blood pressure (p = 0,000 < Î± = 0,01). There were changes in mean blood pressure before and after Prolanis exercise two times per week and there times perweek. Conclusion: In the two groups, there were significant decreases of systolic and diastolic blood pressures after Prolanis exercise for 4 weeks consecutively. Keywords: senam Prolanis, hypertensionÂ Abstrak: Hipertensi merupakan salah satu penyakit degenerative yang banyak ditemukan di Indonesia, ditandai oleh kenaikan tekanan darah diatas nilai normal yang dapat diakibatkan oleh berbagai macam faktor. Penelitian ini bertujuan untuk mengetahui pengaruh senam Prolanis terhadap penderita hipertensi. Jenis penelitian ini ialah ekperimental lapangan dengan pre-post test one group design. Sampel penelitian berjumlah 25 orang lansia yang diperoleh melalui purposive sampling. Senam Prolanis dilakukan selama 4 minggu. Analisis data menggunakan uji t berpasangan. Hasil penelitian memperlihatkan terdapat perbedaan bermakna antara tekanan darah sistolik awal dan akhir pada latihan 2 kali/minggu (p = 0,003 <Î± =0,001); antara tekanan darah diastolik awal dan akhir pada latihan 2 kali/minggu (p = 0,002 <Î± =0,001); antara tekanan darah sistolik awal dan akhir pada latihan 3 kali/minggu (p = 0,000 <Î± = 0,01); dan antara tekanan darah diastolik awal dan akhir pada latihan 3 kali/minggu (p = 0,000 <Î± = 0,01). Terdapat perubahan rerata tekanan darah sebelum dan sesudah latihan senam baik pada latihan 2 kali/minggu maupun 3 kali/minggu. Simpulan: Pada kedua kelompok latihan terdapat penurunan bermakna tekanan darah sistolik dan diastolik setelah senam Prolanis selama 4 minggu berturut-turut.Kata kunci: senam prolanis, hipertensi